Guest Editorial: Role of Classification and Cataloging in the Information Age - Satyanarayan, N.R. (DESIDOC Journal of Library & Information Technology, 2003)
Ever Since man began recording information,it made little difference to him whether the information is recorded as baked in clay tablet,written on papyrus scroll,printed in books,or available in electronic form or digital libraries.But he had been cantinously facing the problem of storing and organising these records ,so that these could be located easily whenever needed.Thenarose the need to index and classify the literature,and subsequently many systems of indexing and classification have been deviced.Manual methods of indexing and classification arew time consuming and require skilled personnel.of late,the challenges is to develop ways and means of applying computer technology for the analysis of natural language text.It is aimed to design and derive automated processor for indexing and classifying documents and improving retrieval technigues.The First and foremost question therefore is whether computers can be used for classification and whether human classification can be superseded by computerised techniques?Secondly,how far computers can be adopted for retrieval techniques and how manual catalogues can be replaced by digital catalogues. http://dx.doi.org/10.14429/dbit.19.3.3482